Peter and the Wolf - Prokofiev, Sergey, 1891-1953.; PaleTcek, Josef (Natick, MA : Picture Book Studio, 1987)
Retells the orchestral fairy tale of the boy who, ignoring his grandfather's warnings, proceeds to capture a wolf.
Translation of: Petdi8a i volk.
Cover title: Peter & the wolf.
"A Michael Neugebauer book."
Keywords: Fairy tales